(3MhGT Ydi GdYOIs - (3Ndjd Hf GdZGRi GdbRejfis; (3CHh LYaQ GdWhSj , CHh LYaQ eMeO Hf GdMSf Hf Ydj GdWhSj, CHh LYaQ GdWhSj,J (B460 (3g` s
(3ChdgG (B:s
(3eG HYO ajbhd GdZfi HQHg YeG ShGg Ndjd Hf GdZGRi GdbRhjfi s
(3BNQgG (B:s
(3dCf dg Cf jbhd GfeG GSJOd Ydi CUd GdMLjI dG Ydi GdbWYjI CjVkkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO PcQ GdYfhGf GdCUdi (B[(3GdYOI ai CUhd GdTjYI(B] (3aj EjVGM Gdecfhf (B95/2 s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis